Java Language Learning Media Folk Story Material Using Multimedia Based Demonstration Methods - Innalita Lake Fan; Santi Widiastuti (International Journal of Graphic Design, 2023)
Based on the results of observations, the learning method used at SMP Negeri 35 Semarang is in the form of lectures, discussions, questions and answers using books . The learning methods that have been applied so far have not had enough impact on the level of students' understanding of the material taught by the teacher. The method used was less successful because of the lack of visualization so that students felt bored and fed up. This research offers a solution for utilizing multimedia with a demonstration method through interesting learning media where computer media can display images, text, audio and video so that folklore can be better visualized and attract students and the learning process can be fun. This research uses the Research and Development (R n D) product development method using 6 of the 10 research stages . The results of the research show that from the media expert validation test, material validation test and user validation test results, the product can be said to be effective and suitable for use.